SILIKON TERLARUT UNTUK PERTUMBUHAN DIATOM - Hanny Meirinawati (Pusat Penelitian Oseanografi LIPI, 2018)
DISSOLVED SILICON FOR DIATOM GROWTH. Silicon is the second most abundant element in the earth’s crust. Silicon is an essential nutrient for diatom growth (Bacillariophyceae). Diatom require dissolved silicon to build silicate cell walls (frustule). Factors regulating diatom growth rate are cell size, concentration, heat, temperature, and concentration of Fe and Zn. The main source of dissolved silicon in the ocean is chemical weathering of rocks. The availability of dissolved silicon plays an important role in controlling the biogeochemical that regulates primary production, atmospheric CO, climate and ocean circulation. Changes in Si:N and Si:P ratios can affect the phytoplankton composition. Beside that, the function of silicon can reduce carbon dioxide levels from the atmosphere. This paper aims to provide information on the process of the occurrence of dissolved silicon in the sea and the function of dissolved silicon especially for diatom growth.